A clinical and mycological study of dermatophytosis in a tertiary care hospital - Munuswamy, Rajesh; Subramanian, Pramodhini (International Journal of Research in Dermatology, 2021)
Background: With changing climatic conditions, socio-demographic profile, economic conditions and occupational profile of the population, the profile of the dermatophyte infections is also changing. Hence, the study was done to find out the prevalence of various clinical pattern of dermatophytosis and correlate the clinical diagnosis with KOH positivity and fungal culture positivity. Methods: This prospective observational study was conducted in a tertiary care hospital, Puducherry. The study included patients presenting to the dermatology outpatient department with skin lesions suggestive of dermatophyte infections between January 2016 to July 2017. The KOH test and fungal culture were done. Results: The mean age of the patients was 33.65±11.61 years, with the majority belonging to 16 to 30 years of age group. There was a high male preponderance 72% with male:female ratio of 2.57:1. The most common clinical diagnosis was Tinea corporis in 47.50% of the population., followed by Tinea Unguium in 28% and Tinea cruris in 19.50%. KOH positivity was seen in 86 (43%) out of 200 cases in the study population. The culture was positive in 55 (27.50%) of the study population. The most common organism isolated in culture was Trichophyton mentagrophyte (10%), followed by Trichophyton rubrum (9.5%) and Trichophyton tonsurans (5.5%). 55 (27.5%) of the people had both culture and KOH positive. Conclusions: Dermatophyte infections commonly affect the young and economically productive age group of 16 to 30-year, with high male preponderance. KOH tends to show a higher proportion of positivity as compared to culture.